Implementing the Theory of Consumption Value on Green Products Purchase Intention: A Green Self-Identity Perspective - Indraswari, Nurul Myristica (Proceedings International Conference on Education Innovation and Social Science, 2024)
Green self-identity and consumption values are crucial antecedents of consumer sustainability behavior. By integrating the theory of consumption values and the self-identity approach, this study explores the relationship between green self-identity, consumption values (functional, conditional, and emotional value), and green products purchase intention. Data were collected from 242 respondents residing in Yogyakarta through a questionnaire survey. Using the PLS-SEM method, the results are that green self-identity has a significant positive effect on functional, conditional, emotional value, and green products purchase intention and also found that conditional value mediates the relationship between green self-identity and green products purchase intention. The results imply that interventions targeting green self-identity are a promising way to promote sustainable consumption behavior using green products. In addition, the results findings also have important implications for the development of markets that sell green products based on self-identity and consumption value.